Burden and risk factors of snakebite in Mopeia, Mozambique: Leveraging larger malaria trials to generate data of this neglected tropical disease. - Emma O'Bryan; Saimado Imputiua; Eldo Elobolobo; Patricia Nicolas; Julia Montana; Edgar Jamisse; Humberto Munguambe; Aina Casellas; Paula Ruiz-Castillo; Regina Rabinovich; Francisco Saute; Charfudin Sacoor; et al. (Public Library of Science (PLoS), 2023)
Background Snakebite is a neglected disease that disproportionally affects the rural poor. There is a dearth of evidence regarding incidence and risk factors in snakebite-endemic countries. Without this basic data, it will be impossible to achieve the target of a 50% reduction of snakebite morbidity and mortality by 2030 as set by the World Health Organization. Methods This was a descriptive analysis nested in a 2021 community-based demographic survey of over 70,000 individuals conducted in Mopeia, Mozambique, in preparation for a cluster randomized trial to test an intervention for malaria. We describe the incidence rate, demographics, socioeconomic indicators and outcomes of snakebite in this population. Findings We found the incidence of self-reported snakebite in Mopeia to be 393 bites per 100,000 person-years at risk, with 2% of households affected in the preceding 12 months. Whilst no fatalities were recorded, over 3,000 days of work or school days were lost with an individual household economic impact higher than that of uncomplicated malaria. 1 in 6 of those affected did not fully recover at the time of the study. We found significant relationships between age older than 15, use of firewood for household fuel, and animal possession with snakebite. Conclusions This study exposes higher than expected incidence and burden of snakebite in rural Mozambique. Whilst snakebite elimination in Mozambique seems unattainable today, it remains a preventable disease with manageable sequelae. We have shown that snakebite research is particularly easy to nest in larger studies, making this a practical and cost-effective way of estimating its incidence.